Direct Fixation of Fractures of the Posterior Malleolus Through a Postero-Medial Approach - Andonov Y.; Parashkevova P. (Acta Medica Bulgarica, 2022)
Background and objective: Fractures of the posterior malleolus have long been neglected in the past. The decision for their fixation should be based on plain lateral radiographs. Recent studies have emphasized the important biomechanical function of the posterior tibial ridge. This has caused a trend towards more aggressive surgical treatment. The aim of this study was to present our experience with the direct fixation of complex ankle fractures engaging the posterior malleolus. We also tried to clarify the advantages and limitations of the posterior-medial surgical approach.